KOLABORASI ILUSTRASI DAN TEMBANG DOLANAN DALAM PENCIPTAAN MEDIA EDUKASI COVID-19 DI SURAKARTA - Basnendar Herry Prilosadoso; Waluyo; Roman Aqviriyoso (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2021)
The Covid-19 outbreak has attacked the community, where the Indonesian Government has handled the pandemic outbreak from health, social, politicaDolanan Song, Illustration, Covid-19, Education, Elementary School Students.l, economic and other related aspects. Various educational media, information, and publications regarding the prevention and spread of this virus have also been carried out in multiple ways and with multiple media. Dissemination of information about the Corona outbreak is needed by all groups, from all age groups, economic status, gender, demographics and other aspects. Likewise, for elementary students, at that age, the information can be used as a guide later, both now and future. An appropriate media for segmentation is needed so that the information presented is acceptable and attractive. Alternative media for illustrated collaboration with tembang dolanan contain moral teachings and conveying media that can apply Dolanan Song, Illustration, Covid-19, Education, Elementary School Students.in preserving mother tongue and character education. The purpose of creating art is children's illustration work and dolanan songs containing interesting material and publication media regarding the prevention and spread of the Covid-19 virus to elementary school students. The method of creating artwork has 6 (six) stages, namely: Discovery, Interpretation, Ideation, Experimentation, Evolution, and Implementation. Through this media, it hoped that it could increase understanding and knowledge, especially elementary school students, in preventing and overcoming the Covid-19 outbreak so that the attack can soon subside. Keywords: tembang dolanan, illustration, Covid-19, education, elementary school students.